STUDENT WELLBEING INDEX AND ITS INFLUENCING FACTORS IN AN ENGLISH EDUCATION PROGRAM - Nanik Retnowati; Dewi Suriyani Djamdjuri; Nuraeni Nuraeni; Eva Nurmayasari (ENGLISH, 2022)
Wellbeing is undoubtedly important in education and has become the focus of program orientation in some institution. As a hidden curriculum, all lecturers should apply their own techniques to promote student wellbeing. This study is trying to identify the index of students' wellbeing and the influencing factors. There were 34 students as the participants of the study. The data was taken by distributing questionnaire and conducting an interview. The result showed that student wellbeing index reached 75.5, under good category. There are two factors that constitute student wellbeing; the supporting factors and the obstacle factors. The supporting factors identified are lecturers, study program, friends, and future career. The obstacle factors are online learning, student-self competences, and assignment or material. This study recommended the institution to maintain and improve student wellbeing index by promoting explicit design of wellbeing teaching learning process in its curriculum.